Psychotherapy as a system and the need for “openings”: Examples of the systemic perspective of cognitive behavioral psychotherapy - Καλαντζή - Αζίζι, Αναστασία; Γαλανάκη, Ευαγγελία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF